Landscape and Englishness - Burden, Robert; Kohl, Stephan (Rodopi, 2006)
In the papers collected in this, the first volume of the Spatial Practices series, Englishness is reflected in the spaces it occupies or dwells in. Broadly influenced by a renewed and growing interest in questions of cultural identity, its emergence in Victorian theories and fictions of nationality, and the new cultural geography, the papers cover a rich variety of spaces and places which have been appropriated for cultural meanings: the rural countryside and farmland of the Home Counties in the early nineteenth century as Arcadian idyll in Cobbett, as the land to die for in war propaganda, an.
Keywords: England -- Historical geography.; Cultural landscapes -- England.; Landscapes -- Symbolic aspects -- England.; National characteristics, English.; Angleterre -- Géographie historique.; Paysages culturels -- Angleterre.; Paysages -- Aspect symbolique -- Angleterre.; Anglais.; HISTORY -- Historical Geography.; Cultural landscapes; Historical geography; Landscapes -- Symbolic aspects; National characteristics, English; England; Electronic book.